Analisis Pembagian Kerja UPTD PPA dan Polresta Jambi dalam Penanganan Kasus Kekerasan Seksual terhadap Anak - Anandra Triwidodo; Riri Maria Fatriani; Wahyu Rohayati; Dimas Subekti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Sexual violence against children in Jambi City continues to show a fluctuating trend, with 32 cases in 2022, decreasing to 24 in 2023, and increasing again to 33 in 2024. This condition emphasizes the importance of strengthening cross-sector case handling between the UPTD PPA Jambi City and the Jambi Police in cases of sexual violence against children. This study aims to analyze the division of labor between the two institutions using the coordination theory according to Hasibuan (2006), which includes indicators of unity of action, communication, division of labor, and discipline. The method used is a qualitative approach through in-depth interviews, documentation, and data triangulation to ensure the validity of the findings. The results show that coordination between the UPTD PPA Jambi City and the Jambi Police has generally been running well, especially in the aspects of unity of action and discipline, as reflected in the alignment of goals and a fairly rapid response in handling cases. Communication between the two agencies has also been ongoing through formal and informal channels to expedite case response. The division of labor has been aligned with each agency's respective authority, with the UPTD PPA focusing on victim assistance and psychological support, while the police handle law enforcement. However, the lack of formal SOPs and MoUs poses a barrier to strengthening sustainable institutional integration. The implications of this research emphasize the need to strengthen formal mechanisms, regular evaluation forums, and formal cooperation agreements to enhance effective coordination and comprehensive protection for child victims.